Galen, Body and Soul in Vita Cyrilli XI, 13–20 - Daiber, Thomas (Studia Ceranea, 2021)
The paper points to a hitherto not recognized quotation from Galen in the Old Church Slavonic Life of S. Cyril of the 9th century (chapter XI, 15) which demonstrates the Galenic maxim “contraria contrariis curentur”. The Galenic argument is brought forth by the Christian philosopher Cyril in a discussion with Jewish theologians. The paper firstly demonstrates that the author of VC does not only enrich Cyril’s speech with allusions to Biblical formulations but makes also the Jewish interlocutors use a direct quotation from Paul’s Epistle to the Colossians. The Christian and Jewish arguments complement each other leading to the ultimate Christian answer that Christ is the real physician to heal body and soul. In contextualizing the findings and pointing to another passage of Vita Cyrilli the paper shows, that the metaphor of “Christ, the physician” both times occurs in a context, where the Original sin is the main topic. Finally, the paper is concerned with the rhetoric of the metaphor and the limits of what can be possibly expressed by it. The ultimate healing in a Christian sense is expressed in the faith into bodily resurrection and thus transcends the comparison with concrete physical therapy. In contrast to concrete bodily health the qualities of a “body of the resurrection” cannot be positively named and thus are designated by the metaphor of “enjoying the fruit” in the heavens.